The SIROFLOC process for treating turbid waters of Thai sources - Shanmuganantha, Sivasubramaniam; Fude, I.; Shin, H.S.; Hanaki, K.; Fish, E.J.; Wang, R.R.; NORAD, Norway (Bangkok : Asian Institute of Technology, 1986)
Most water treatment involves coagulation-flocculation process in the removal of turbidity and color. The SIRIFLOC Process is a recently developed coagulation-adsorption process where recoverable magnetite is used as coagulant-adsorbent instead of conventional coagulants. The SIROFLOC Process is being used in Australia, United Kingdom and Republic of China as a successful alternative to conventional processes. The applicability of SIROFLOC Process to waters of Chao Phrya River of Thailand in removing turbidity and color was considered on a laboratory scale in this study. Several samples were jar-tested with pH, dosage of magnetite and dosage of polyelectrolyte as controlling parameters to study the effect of the above controlling parameters on the removal of turbidity and color. Similar studies were performed simultaniously with alum instead of magnetite as coagulant for comparison purposes. Results indicated that with initial turbidities ranging from 25-160 NTU and obtained during September 1985 - January 1986 period, SIROFLOC Process produced effluents of turbidity and color less than 5 NTU and 50Hazen respectively. The optimum conditions varied from sample sample. Removal of turbidity rather than removal of color governed such optimum conditions. Dosages of magnetite from 0.5-1.5% wjw were found to be sufficient. Dosage of cationic type polyelectrolyte in the range of 0.25-0.50 mgjl gave satisfactory results. pH closer to the natural pH (about 7.0) was found to be quite appropriate. For initial turbidities less than 48 NTU both alum and magnetite were equally effective but beyond 48 NTU magnetite gained superiority over alum. Magnetite was found to be superior to alum for initial color values greater than 150Hazen. Regeneration of Magnetite was very effective.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M. Eng.) - Asian Institute of Technology, 1986
Keywords: Sewage -- Purification -- Flocculation